The Association of MTHFR C677T and A1298C Polymorphisms with Methotrexate Response and Toxicity in Psoriasis - Sauvarat Auepemkiate (Siriraj Medical Journal, 2016)
Background: Methotrexate (MTX) is used to treat psoriasis with various side effects and responsiveness. No predictive indicator of responsivenessor toxicityis available. Objective: Tostudytheassociationof the C677T and A1298C polymorphisms inthe methylenetetrahydrofolate reductase (MTHFR) gene withthe responsiveness andside effectsof MTX in psoriatic Thai patients. Methods: Thepolymorphisms wereidentifiedfrom86MTX-treatedpatientsinthreehospitalslocatedinsouthern Thailandusing allele-specificPCR. Thepatients were monitored for the effectiveness and toxicity of the MTX. Results: The C677T genotype frequencies for C/C, C/T, and T/T were 70.9, 26.8, and 2.3%, respectively, and those of the A1298C genotypes for A/A, A/C, and C/C were 57, 32.5, and 10.5%, respectively. Seventy-three patients (87.9%) respondedtoMTX. Thenon-respondershadhighercombinedfrequenciesof C/T and T/T of the C677T (50%) thanthe responders (24.7%) withnostatistical significance (p=0.131),buthada lower frequency of CC genotypeof the A1298C, althoughnot statisticallydifferent (p=0.691). Elevenpatients (12.8%) suffered toxicity. No association of thesepolymorphisms and MTX toxicity was found. Conclusion: The studydidnot show anassociationbetweenthese MTHFR polymorphisms with MTX response and toxicityin thesepatients.